Amplification of N-Myc is associated with a T-cell-poor microenvironment in metastatic neuroblastoma restraining interferon pathway activity and chemokine expression. (3rd June 2017) - Layer, Julian P.; Kronmüller, Marie T.; Quast, Thomas; Boorn-Konijnenberg, Debby van den; Effern, Maike; Hinze, Daniel; Althoff, Kristina; Schramm, Alexander; Westermann, Frank; Peifer, Martin; Hartmann, Gunther; Tüting, Thomas; et al.
ABSTRACT: Immune checkpoint inhibitors have significantly improved the treatment of several cancers. T-cell infiltration and the number of neoantigens caused by tumor-specific mutations are correlated to favorable responses in cancers with a high mutation load. Accordingly, checkpoint immunotherapy is thought to be less effective in tumors with low mutation frequencies such as neuroblastoma, a neuroendocrine tumor of early childhood with poor outcome of the high-risk disease group. However, spontaneous regressions and paraneoplastic syndromes seen in neuroblastoma patients suggest substantial immunogenicity. Using an integrative transcriptomic approach, we investigated the molecular characteristics of T-cell infiltration in primary neuroblastomas as an indicator of pre-existing immune responses and potential responsiveness to checkpoint inhibition. Here, we report that a T-cell-poor microenvironment in primary metastatic neuroblastomas is associated with genomic amplification of the MYCN (N-Myc) proto-oncogene. These tumors exhibited lower interferon pathway activity and chemokine expression in line with reduced immune cell infiltration. Importantly, we identified a global role for N-Myc in the suppression of interferon and pro-inflammatory pathways in human and murine neuroblastoma cell lines. N-Myc depletion potently enhanced targeted interferon pathway activation by a small molecule agonist of the cGAS-STING innate immune pathway. This promoted chemokine expression including Cxcl10 and T-cell recruitment in microfluidics migration assays. Hence, our data suggest N-Myc inhibition plus targeted IFN activation as adjuvant strategy to enforce cytotoxic T-cell recruitment in MYCN -amplified neuroblastomas.